Distributed cognition in Enlightenment and Romantic culture - Anderson, Miranda; Rousseau, G. S. (George Sebastian); Wheeler, Michael, 1960- (Edinburgh history of distributed cognition., 2019)
Revitalising our reading of 18th century works specifically in the fields of the history of the book, literary studies, material culture, art history, philosophy, technology, science and medicine, this volume brings recent insights in cognitive science and philosophy of mind to bear on the distributed nature of cognition.